2022
DOI: 10.1021/acs.jpca.2c05803
|View full text |Cite
|
Sign up to set email alerts
|

Alternating 1-Phenyl-2,2,2-Trifluoroethanol Conformational Landscape With the Addition of One Water: Conformations and Large Amplitude Motions

Abstract: The 1:1 adduct of 1-phenyl-2,2,2-trifluoroethanol (PhTFE), a chiral fluoroalcohol, with water was investigated using chirped pulse Fourier transform microwave spectroscopy and computational methods. While PhTFE itself was predicted to have three minima, I (gauche+), II (trans), and III (gauche−), only I and II were stable and only I was observed experimentally. A systematic search of the PhTFE···H2O conformational landscape identified 110 stable minima, 14 of which are within a 15 kJ mol–1 energy window. Rotat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 72 publications
1
26
0
Order By: Relevance
“…The Boltzmann averaged IR and VCD spectra of the three most stable conformers of DHEA were simulated using three different basis sets: cc-pVTZ, 6-31++G(2d,p) and def2-TZVPD. The B3LYP-D3BJ/def2-TZVP has been utilized extensively by the rotational spectroscopic community and the inclusion of an additional set of diffuse functions, i.e., def2-TZVPD, appeared to provide even better performance for conformational geometries and their energy ordering, with little additional computational cost [ 40 ]. It is interesting to compare its performance with the other two basis sets often used by the VCD and ROA community.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The Boltzmann averaged IR and VCD spectra of the three most stable conformers of DHEA were simulated using three different basis sets: cc-pVTZ, 6-31++G(2d,p) and def2-TZVPD. The B3LYP-D3BJ/def2-TZVP has been utilized extensively by the rotational spectroscopic community and the inclusion of an additional set of diffuse functions, i.e., def2-TZVPD, appeared to provide even better performance for conformational geometries and their energy ordering, with little additional computational cost [ 40 ]. It is interesting to compare its performance with the other two basis sets often used by the VCD and ROA community.…”
Section: Resultsmentioning
confidence: 99%
“…It has been recognized from some previous ab initio MD studies [ 28 ] and DFT VCD solvation studies [ 66 ] that using the spectroscopic properties at the predicted minima may not be enough to reproduce the observed spectral features in solution. More recently, some rotational spectroscopic studies [ 40 , 67 ] demonstrated clearly that the experimental electric dipole components and nuclear quadruple coupling constants could be very different from those predicted at the minima because of large amplitude motions. In addition, the associated VCD simulations showed that the vibrationally average features can be dramatically different from those at the minima [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations